Economic Policy Uncertainty in Europe: Spillovers and common shocks - Jaromír Baxa; Tomáš Šestořád (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This paper proposes a novel approach to decompose the Economic Policy Uncertainty indices of European countries into the common and country-specific components using the time-varying total connectedness. Then, by employing a Bayesian panel VAR model, we assess how common and country-specific uncertainty shocks influence economic activity, prices, and monetary policy, with the shocks identified using zero and sign restrictions. Our results reveal that only common shocks have significant effects on all macroeconomic variables. This result is robust across alternative samples and structural identifications. Therefore, our findings imply that policymakers should focus on uncertainty shocks that are synchronized across countries.
Keywords: C32; F42; F45; 330; Common uncertainty; economic policy uncertainty; panel VAR; spillovers